Dinamika multikulturalisme dan tantangan toleransi di Indonesia kontemporer - Ramadhan, Muhammad Raihan Fajar (Maliki Interdisciplinary Journal, 2026)
Indonesia is multicultural country with diverse ethnicities, cultures, languages, and religions. This diversity becomes a strength in building a harmonious society through the value of tolerance. However, in this contemporary era, technological development and globalization have brought new dynamics to Indonesian society. As a result, various challenges to tolerance have emerged, making efforts to preserve the nation’s moral values and tolerance increasingly important. This article aims to examine the dynamics of multiculturalism and the challenges of tolerance in contemporary Indonesia. The discussion also covers various factors causing the dynamics of multiculturalism in the contemporary era, the challenges faced, and efforts to maintain national unity without neglecting noble values. Therefore, this article explains the possible impacts and the actions that should be taken by Indonesian citizens.